MEWUJUDKAN KESADARAN BERAGAMA SISWA; STUDI DESKRIPTIF PSIKOLOGIS PADA SISWA KELAS VIII SMP NEGERI 5 NGAWI - Budi Sunariyanto (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2014)
SMP Negeri 5 Ngawi efforts in creating religious culture in schools, especially religious awareness students have some program activities. This is done as a means of support in the realization of religious consciousness in students because the learning process of Islamic Religious Education class can not be expected to be optimal in creating religious awareness in students. Based on the above background, the issues to be addressed in this study is how the effort to create awareness of religious schools on the students of SMP Negeri 5 Ngawi. In this study the authors used a descriptive approach in which psychological researchers describe the circumstances in a holistic manner and then analyze it in the form of words in order to obtain the views as his world view. This study describes and analyzes the researcher an overview of the religious consciousness of students of SMP Negeri 5 Ngawi and the efforts made in creating awareness of religious schools on the students of SMP Negeri 5 Ngawi. Results of research conducted found that: first, the establishment of religious awareness in students of SMP Negeri 5 Ngawi is due to the synergy of integrated prorgam on religious activities conducted by the school. Second, the means to raise awareness in students of religion are closely related to the learning process among the Islamic Religious Education class, the school efforts in this regard is the concept of character education and learning methods against these problems in Islamic Education. Third, the realization of religious awareness in students of SMP Negeri 5 Ngawi is inseparable from the moral commitment of all components used to behave in a school based on religious values, one exemplary and disciplined attitude exemplified Principal Junior High School 5 Ngawi